Comparison of group-based outpatient physiotherapy with usual care after total knee replacement: a feasibility study for a randomized controlled trial. (April 2017) - Artz, Neil; Dixon, Samantha; Wylde, Vikki; Marques, Elsa; Beswick, Andrew D; Lenguerrand, Erik; Blom, Ashley W; Gooberman-Hill, Rachael
Objective: To evaluate the feasibility of conducting a randomized controlled trial comparing group-based outpatient physiotherapy with usual care in patients following total knee replacement. Design: A feasibility study for a randomized controlled trial. Setting: One secondary-care hospital orthopaedic centre, Bristol, UK. Participants: A total of 46 participants undergoing primary total knee replacement. Interventions: The intervention group were offered six group-based exercise sessions after surgery. The usual care group received standard postoperative care. Participants were not blinded to group allocation. Outcome measures: Feasibility was assessed by recruitment, reasons for non-participation, attendance, and completion rates of study questionnaires that included the Lower Extremity Functional Scale and Knee Injury and Osteoarthritis Outcome Score. Results: Recruitment rate was 37%. Five patients withdrew or were no longer eligible to participate. Intervention attendance was high (73%) and 84% of group participants reported they were 'very satisfied' with the exercises. Return of study questionnaires at six months was lower in the usual care (75%) than in the intervention group (100%). Mean (standard deviation) Lower Extremity Functional Scale scores at six months were 45.0 (20.8) in the usual care and 57.8 (15.2) in the intervention groups. Conclusion: Recruitment and retention of participants in this feasibility study was good. Group-based physiotherapy was acceptable to participants. Questionnaire return rates were lower in the usual care group, but might be enhanced by telephone follow-up. The Lower Extremity Functional Scale had high responsiveness and completion rates. Using this outcome measure, 256 participants would be required in a full-scale randomized controlled trial.